REAKSI PASAR MODAL DARI DAMPAK PERISTIWA KERUSUHAN MAKO BRIMOB MEI 2018 TERHADAP ABNORMAL RETURN INDEKS LQ45 YANG TERDAFTAR DI BEI - Dewo Adhi Guminto; Maria Assumpta Evi Marlina (Universitas Ciputra Surabaya, 2019)
This research is an event study that aims to determine the difference in the average Abnormal return (AR) before, during and after the Mako Brimob riots. The subject of this study is the LQ45 index company that has fulfilled the criteria, namely the company does not conduct corporate actions such as the announcement of stock split, right issue, merger & acquisition and devidend in the observation period, which is five days before the riot, one day during the riot (May 9, 2018) and five days after the riots. The results of the data normality test found that the data in this study were normally distributed. p-value shows the number 0.412. The results of the different tests using independent Sample T-Test (H1) showed no difference in the average abnormal return before and during the Mako Brimob riots (ρ = 0.050). The results of different tests using independent Sample T-Test (H2) showed no difference in the average abnormal return during and after the incident of the Mako Brimob riots (ρ = 0.117). The results of different tests using Paired Sample T-Test (H3) showed no difference in the average abnormal return before and after the incident of the Mako Brimob riots (ρ = 0.77).